Biological aspects and first record of Leucothyreus alvarengai Frey (Coleoptera: Melolonthidae: Rutelinae) in sugarcane (Saccharum officinarum L) (Poaceae) fields of Mato Grosso do Sul state, Brazil - GILMAR V. COUTINHO; CRÉBIO J. ÁVILA; ELIAS S. GOMES; EDUARDO N. COSTA; SÉRGIO R. RODRIGUES; IVANA F. DA SILVA (Anais da Academia Brasileira de Ciências, 2023)
Abstract Larvae of Leucothyreus spp. have been reported causing damage to several crops in Brazil. From May 2012 to April 2013, adults and immatures of Leucothyreus alvarengai Frey (Coleoptera: Melolonthidae: Rutelinae) samples were obtained from sugarcane (Saccharum officinarum L.) (Poaceae) fields in the municipalities of Naviraí and Nova Andradina, Mato Grosso do Sul, Brazil. Adults were collected with the aid of light traps, whereas immatures were sampled by opening two trench sizes (30 x 30 x 30 cm and 80 x 50 x 40 cm) in the soil, beside the plants. The collected larvae were reared in laboratory conditions, fed by sugarcane seedlings. The biological cycle of L. alvarengai was completed in 230 days, displaying three larval instars with mean size of the cephalic capsule of 1.68, 2.46, and 3.00 mm for the first, second, and third instar, respectively. Adults were collected in greater numbers in December 2012, and first-instar larvae were observed as of January 2013. Conversely, pupae were observed in the field from July 2012 to January 2013. This is the first record of larvae and adults of L. alvarengai in sugarcane fields in Mato Grosso do Sul state, contributing with the knowledge about its biology and temporal distribution in the field.